Bound state solutions for a class of Nonlinear Elliptic Equations with Hardy potential and Berestycki–Lions type conditions. (August 2022) - Liu, Jiu; Duan, Yu; Liao, Jia-Feng
Abstract: By using the variational methods, a class of Nonlinear Elliptic Equations with the Hardy potential and Berestycki-Lions type conditions is studied and a bound state solution is obtained.